2020
DOI: 10.12688/wellcomeopenres.15829.1
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cardiovascular disease and risk of premature coronary heart disease: A matched case-control study

Abstract: Background: Self-reported family history of cardiovascular disease (CVD) is an independent risk factor for future coronary heart disease (CHD) events. However, inclusion of family history of CVD in the traditional risk scores failed to improve risk prediction of CHD. It is proposed that family history of CVD may substantially increase the risk of CHD among younger individuals. Methods: We conducted a matched case-control study with 170 hospital-based premature CHD patients (<55 years in men and <65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Unlike controllable risk factors, such as diabetes history, a family history of CHD is a risk factor that cannot be prevented. In a previous study, approximately one-quarter of the population with a family history of CHD was at high risk of CHD, requiring premature intervention to prevent the occurrence of PCHD [38]. A study based on a community population in the United States showed that the prevalence rate of PCHD in young people with a positive family history of CHD was approximately 75% [39].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike controllable risk factors, such as diabetes history, a family history of CHD is a risk factor that cannot be prevented. In a previous study, approximately one-quarter of the population with a family history of CHD was at high risk of CHD, requiring premature intervention to prevent the occurrence of PCHD [38]. A study based on a community population in the United States showed that the prevalence rate of PCHD in young people with a positive family history of CHD was approximately 75% [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals with a family history of the disease comprise a large group (at least 24% of the total adult population in India). 12 Hence, our approach could have substantial public health benefits by preventing future cardiovascular events if applied at the population level. Similar family-based studies with population-wide coverage will help us to understand the effect of this intervention model at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 A family history of premature coronary heart disease is associated with a 1•5-7 times higher risk of future cardiovascular events. [11][12][13] Although the excess risk was initially thought to be due to genetic factors, substantial evidence shows that it is due to shared environment, and similarity in behaviour and belief systems within families. 14 Furthermore, modifiable traditional risk factors jointly mediate a substantial portion of the increased risk of the disease conferred by a positive family history.…”
Section: Introductionmentioning
confidence: 99%